F3/Contactin promotes hippocampal neurogenesis, synaptic plasticity, and memory in adult mice. Issue 12 (9th September 2013) - Puzzo, Daniela; Bizzoca, Antonella; Privitera, Lucia; Furnari, Dario; Giunta, Salvatore; Girolamo, Francesco; Pinto, Marco; Gennarini, Gianfranco; Palmeri, Agostino
ABSTRACT F3/contactin, a cell‐adhesion molecule belonging to the immunoglobulin supergene family, is involved in several aspects of neural development including synapse building, maintenance and functioning. Here, we examine F3/contactin function in adult hippocampal neurogenesis, synaptic plasticity, and memory, using as a model TAG/F3 transgenic mice, where F3/contactin overexpression was induced under control of regulatory sequences from the human TAG‐1 (TAX‐1) gene. Transgenic mice aged 5 (M5) and 12 (M12) months exhibited an increase in hippocampal size, which correlated with positive effects on precursor proliferation and NeuN expression, these data suggesting a possible role for F3/contactin in promoting adult hippocampal neurogenesis. On the functional level, TAG/F3 mice exhibited increased CA1 long‐term potentiation and improved spatial and object recognition memory, notably at 12 months of age. Interestingly, these mice showed an increased expression of the phosphorylated transcription factor CREB, which may represent the main molecular correlate of the observed morphological and functional effects. Altogether, these findings indicate for the first time that F3/contactin plays a role in promoting adult hippocampal neurogenesis and that this effect correlates with improved synaptic function and memory. © 2013 Wiley Periodicals, Inc.